The Fabulous Furry Freak Brothers grass roots and other follies - Shelton, Gilbert 1940-; Sheridan, Dave 1943-1982; Mavrides, Paul 1952- (Fantagraphics, 2023)
"The third release in our Freak Brothers Follies series follows the Fabulous Furry Freak Brothers back to their hippie origins! The Fabulous Furry Freak Brothers -- Freewheelin' Franklin, Phineas, and Fat Freddy -- score some sinsemilla from a country cousin, start a softball league to score free drinks, adopt a possessed parakeet that outwits the D.E.A., and inadvertently take in a couple of undercover cops as housemates! The title story collects an epic that ran for over six months in newspapers, in which the Brothers, evicted from their apartment, move to the country to get back to nature -- only to discover that nature doesn't want them! Meanwhile, Fat Freddy's Cat adapts much more readily to outdoor living. Then, in a bonus tale, the cat leads the way in the accidental animal rights adventure, "Animal Camp.""--Amazon
Keywords: Fabulous Furry Freak Brothers (Fictitious characters) / Comic books, strips, etc; Comic books, strips, etc / United States; Comic books, strips, etc; Fabulous Furry Freak Brothers (Fictitious characters); United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Graphic novels; Comics (Graphic works); Underground comics; Humorous comics; Comic